Десятирічний ювілей ВУАН: підготовка та втілення (1928–1931 рр.) - Байкєніч, Д. (Український історичний журнал, 2018)
Ідеться про перебіг процесу підготовки відзначення десятирічного ювілею
Всеукраїнської академії наук. На основі архівних та опублікованих документів, мемуарів і наукової літератури аналізується питання формування
концепції проведення врочистих заходів, її трансформація під впливом переформатування української науки. Розглянуто створення, склад і діяльність
ювілейної комісії, що організовувала та контролювала підготовку врочистостей, була посередником у вирішенні поточних питань між установами
та Президією ВУАН і владними органами. Комплексно досліджено основні
напрями підготовки – видавничий та виставковий. У динаміці відстежено
роботу науковців над ювілейними виданнями, зміну концепту змісту праць
і вибірковий друк. Висвітлено підготовку виставок академічних установ та
музейних експозицій, що привернули увагу громадськості до наукових доробків учених. Узагальнено інформацію про фінансування підготовчих робіт і використання наданих коштів. Показано складання установами ювілейних
кошторисів, їх неодноразовий перегляд через вимоги влади. Розглянуто обсяги фінансування з боку урядів СРСР та УСРР. Підкреслено неґативний вплив протистояння радянської влади з академіками ВУАН на функціонування установ академії, зокрема на підготовку до першого ювілею. Виділено чинники, які хронологічно відсунули й, урешті, завадили втіленню ювілейних заходів. The process of preparation of the celebration of the 10th anniversary of the All-
Ukrainian Academy of Sciences is considered in the article. On the basis of the archive
and public documents, memoirs and scientific literature, we can analyze the formation
of the celebration concepts and its transformation under the influence of reformation
of the Ukrainian science. The creation, composition and activities of the Anniversary
Commission, which organized and controlled the preparation of the celebrations and
was an intermediary between the Presidium of All-Ukrainian Academy of Sciences
and the authorities institutions in solution of current issues. The main directions of
preparation publishing and exhibition are explored in details. The work of scientists
on the Anniversary editions, changing of the concept of the content of work and
selective printing was tracked in dynamics. The preparation of exhibitions of academic
institutions and museum expositions, the exhibits of which attracted the attention of
the public to scientific development scientists was also highlighted. The information on
the financing of preparatory work and the use of funds provided was summarized. The
compilation of the anniversary financial reports was presented by organizations, their
repeated revision due to the demands of the authorities. Was considered the amount
of funding from the governments of the USSR and the Ukrainian SSR. The negative
impact of the confrontation of the Soviet government with academics of the Ukrainian
Academy of Sciences on the functioning of the Academy institutions, in particular, on
preparations for the first anniversary was underlined. The factors that chronologically
pushed aside and finally prevented the implementation of the anniversary events are highlighted.